(untitled) (Modern Problems of Metallurgy, 2025)
This research focuses on improving the reliability of simulating the operation of induction motors when solving technical and economic problems related to the selection of protection systems for electric drives operating in industrial power networks with poor power quality. The presence of voltage asymmetry, harmonic distortions, and other power quality issues in workshop networks significantly affects the performance and service life of induction motors, increasing energy losses and maintenance costs. The article proposes a power and economic model that allows conducting computational experiments to determine the optimal solution for improving power supply quality. A key element of the model is the system for generating and controlling linear voltage parameters, which ensures compliance of the simulated signals with their statistical regularities observed in real industrial conditions. The research introduces adaptive algorithms for the continuous and simultaneous assessment of average values, variances, autocorrelation, and cross-correlation functions of voltage harmonics. Mathematical expressions for their correction during the accumulation of information are presented. Structural schemes of control systems for both analog and digital modeling of voltage processes are proposed, allowing for real-time monitoring of the reliability of generated data. The simulation results were verified through statistical hypothesis testing for the average values and variances of the generated voltage harmonics. Experimental studies were carried out in the rolling shop No. 1 of Dneprospetsstal LLC, where significant voltage distortions are caused by the operation of powerful semiconductor converters. The results confirmed the adequacy of the proposed modeling approach and its applicability for making economically sound decisions regarding the choice of technical solutions for voltage quality improvement. This work contributes to the field of energy efficiency in industrial enterprises by providing a methodological basis for the reliable simulation of induction motor operation in the presence of distorted power supply conditions. The proposed approach allows reducing the cost and duration of experimental studies by replacing them with validated computational modeling.